The Progressivity Of The First Income Tax In The United Kingdom: Data From 1799/1800 And 1815/1816 - Gelardi, Alexander (Archives of Business Research, 2016)
William Pitt the Younger’s government introduced a national income tax in the United Kingdom in 1799 to help pay for the war against France. When the war ended, income tax was repealed. The tax was unpopular from the beginning and was regarded as being unfair. Progressivity is generally regarded as being a measure of equity. This research looks at the progressivity at the beginning and end of the first UK income tax. Both the Suits and Kakwani indices are used to measure the level of progressivity. It was found that at the beginning the tax was very progressive for taxpayers. However, by the time it was repealed it, the level of progressivity was much reduced.